IMPLEMENTASI WAKAF UANG (Studi terhadap Persepsi Umat Islam Kota Metro Serta Kesiapan Bank Syariah Mandiri dan Kementerian Agama Kota Metro) - Suhairi, Suhairi (P3M STAIN Jurai Siwo Metro, 2011)
This research explores the perceptions of Muslims in Metro City toward waqf money and readiness Islamic Bank and the Ministry of Religious Affairs Metro City. Based on research findings, although the majority of Muslim in Metro City follow Shafi school, but many of them agree and interested in the waqf of money. Bank Syariah Mandiri (BSM) in Metro City, on principle has been prepared by the operational circular letter from BSM center, but BSM in Metro City have not socialized and publicized that they are Islamic Financial Institutions (LKS) as recipient of waqf of Money (Penerima Wakaf Uang/PWU). While the readiness of the Ministry of Religious Metro City is concern, where they have not received and knew Regulation of Minister of Religion No. 4 of 2009 on Registration Administration of waqf of Money. Therefore, socialization of waqf of money in order to implement is very important.Keywords: waqf of money, perception, implementation, nazhir.